Trends in Dietary Supplement Use Among US Adults Between 2009 and 2018. (7th June 2021) - Zhao, Longgang; Tyson, Nyrobi; Liu, Jihong; Hébert, James; Steck, Susan
Abstract: Objectives: A previous study reported that overall use of dietary supplements among United States (U.S.) adults remained stable from 1999 to 2012. However, little is known about trends over the last ten years. We examined trends in dietary supplement use in recent cycles of the National Health and Nutrition Examination Survey (NHANES). Methods: The NHANES, a serial cross-sectional study of noninstitutionalized adults and children residing in the U.S., was used to estimate the prevalence of overall dietary supplements use among adults (age ≥ 19 y) between 2009 and 2018 (five continuous 2-year cycles). Information about dietary supplement use was collected in an in-home interview by asking the participants whether they used any dietary supplements in the preceding 30 days. Survey-weighted prevalence was calculated to be nationally representative of the U.S. population. We also evaluated the trends across cycles and conducted subgroup analyses by age, sex, race/ethnicity, education status, body mass index, and self-reported health status. Results: Over five NHANES cycles, data from 28, 415 adults ≥ 19 y were included in current analyses. The sample size ranged from 5, 600 to 6, 215 across survey cycles. Mean age was 47.2 years. The overall use of any dietary supplements increased between 2009 and 2018 (49.5% in 2009–2010 and 57.4% in 2017–2018, P for trend < 0.001). Use of four or more supplement products also increased from 7.8% to 14.1% between 2009–2010 and 2017–2018 cycles (Ratio = 1.94, 95% Confidence Intervals: 1.52, 2.48, P for trend < 0.001). The observed trend toward increasing was consistent across different age and sex groups, and more pronounced among participants with higher education, higher body mass index, and fair or poor self-reported health status. Conclusions: The overall use of any dietary supplements among U.S. adults increased during the last ten years. The trend was robust among different population groups. Underlying reasons for these trends warrant further investigation. Funding Sources: The author(s) received no specific funding for this work.